The Outburst of Rage and The Divine Dagger : invective poetry and inter-Ṭarīqa conflict in Northern Nigeria, 1949 - Brigaglia, Andrea (Journal for Islamic Studies, 2023)
This paper discusses the conflict between the political establishment of Sokoto and the Tijanis of the province in the late 1940s, focusing on its literary ramifications in the form of Hausa and Arabic invective poetry (hijā’). After locating these poems in their political context, the paper attempts to look at these documents from the point of view of the history of hijā’ as a literary genre. Hijā’ has an old history, rooted in the pre-Islamic Arabic literary tradition. Following islamization, however, the genre acquired an ambivalent status and was often shunned by the religious scholars, who considered it as too profane. The two northern Nigerian cases of invective poetry studied in this paper, on the contrary, were composed by religious scholars and were fundamental as instruments of mobilization of their religious group. One of the two poems here analyzed, in particular, has the form of a ritual meant to cause harm to an opponent. This aspect could be read in the light of an original hypothesis of Ignaz Goldziher, who had suggested that literary invective in the Arab tradition should be traced back to an original prototype which mainly had a ritual/religious function.